Typology The Study Of Hadith Orientalist: Thinking A. Kevin Reinhart In “Juynbolliana, Gradualism, The Big Bang, And Hadith Study In The Twenty First Century” - Hasibuan, Ummi Kalsum (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract This article explores the typology of orientalist hadith studies with a focus on one of the works of orientalist figures, namely: A. Kevin Reinhart with the title "Juynbolliana, Gradualism, The Big Bang and Hadith Study in the Twenty-First Century". The research method in the article is descriptive-qualitative with library research. The purpose of the article is to examine comprehensively the typology of hadith studies, useful for readers in conducting hadith studies and for adding knowledge and insight for readers to think critically. The results of this paper indicate that: first; Kevin is a leading expert at Dartmouth College Hanover, New Hampshire, the United States who was born on February 15, 1952. Second; KR offers the term "gradualism and big bang" as an attempt to make an analogy by it and the study of large (giant) gravity fields that often occur in black holes (meaning that there is no light (emitter) that escapes from the black hole). Third; KR tries to provide a mapping of "counterfeiting and faith" using a model study conducted by Ignaz Goldziher and Josep Schacht. Fourth; Finally, KR would like to try to study the criticism of Sanad hadith academically represented by an orientalist figure who was very involved in his study, namely G.H.A. Juynboll and other scholars who came from the west and were sceptical, such as; Michael Cook, Herberg Berg, Harald Motzki, Gregor Scholer, Norman Calder and Andreas Gorke. There are also other figures, namely; Fuad Sezgin and Nabia Abbot. In addition to examining the science of isnad KR also discusses the authority of sunnah/hadith and the inevitable study of the question of the authenticity of the hadith in which the two themes are represented by the orientalist Jonathan Brown. Keywords: A. Kevin Reinhart, Gradualism dan Big Bang, Pemalsuan dan Iman Abstrak Artikel ini mengeksplorasi tentang tipologi kajian hadis orientalis dengan fokus kepada salah satu hasil karya tulis tokoh orientalis yaitu: A. Kevin Reinhart dengan judul “Juynbolliana, Gradualism, The Big Bang and Hadith Study in the Twenty First Century”. Metode penelitian dalam artikel bersifat deskriptif- kualitatif dengan penelitian yang berjenis pustaka (library research). Tujuan dari artikel adalah ingin mengkaji secara komprehensif terkait dengan tipologi kajian hadis, berguna bagi para pembaca dalam melakukan kajian hadis dan untuk menambah ilmu pengetahuan maupun wawasan bagi para pembaca agar dapat berpikir secara kritis. Hasil dari tulisan ini menunjukkan bahwa: pertama; Kevin merupakan ahli terkemuka di Darmouth college Hanover, New Hampshire, Amerika Serikat yang dilahirkan pada tanggal 15 Februari 1952. Kedua; KR menawarkan istilah “gradualism dan big bang” sebagai usaha untuk dianalogikan olehnya serta kajian mengenai medan grativasi yang besar (raksasa) sering terjadi lubang hitam (maksudnya tidak terdapat cahaya (pemancar) yang lolos dari lubang hitam tersebut). Ketiga; KR berupaya memberi pemetaan terhadap “pemalsuan dan iman” dengan menggunakan model kajian yang dilakukan oleh Ignaz Goldziher dan Josep Schacht. Keempat; Terakhir KR ingin mencoba mengkaji studi kritik sanad hadis secara akademi diwakili oleh tokoh orientalis yang sangat andil dalam studinya adalah G.H.A. Juynboll serta cendikiawan lainnya yang berasal dari barat dan bersifat skeptis, seperti; Michael Cook, Herberg Berg, Harald Motzki, Gregor Scholer, Norman Calder dan Andreas Gorke. Juga terdapat tokoh lainnya, yaitu; Fuad Sezgin dan Nabia Abbot. Selain mengkaji tentang ilmu isnad KR juga membahas tentang otoritas sunnah/hadis serta studi tidak terhindarkannya dari pertanyaan keaslian hadis yang mana kedua tema bahasan tersebut diwakili oleh tokoh orientalis Jonathan Brown. Kata Kunci: A. Kevin Reinhart, Gradualism dan Big Bang, Pemalsuan dan Iman